Investigation of the Effect of Linter Mixer Blade on Seed Lintering Process - Rustam Sulaymonov; O’tkir Norboyev (International Journal on Orange Technologies, 2022)
In order to increase the productivity of the linter, improve the quality of the resulting seeds and fluff, the metal blades of the 5LP linter mixer were equipped with rubber, which is a viscous element, and the mixer was improved. The improved paddle mixer was installed on a 5LP 30-saw linter in the technological laboratory of Pakhtasanoat Scientific Center JSC and comparative studies were carried out with a mixer of a simple design with metal blades. Experiments were carried out with mixing blades and saw teeth in a saw cylinder with a change in distance from 8 mm to 12 mm. During the research period, when using a mixer with blades of a viscous element in the linter, the fluffiness of the seeds after the linter ranged from 6.84% to 8.4%, and the quality of the seeds produced was from 6.84 (abs.)% to 8.4 (abs.)%. )%. , down quality improved from 0.24 (abs.)% to 0.03 (abs.)%. At the same time, the performance of the proposed linter is higher than the performance of a linter with a mixer of a simple design: for seeds from 22 kg/h to 12 kg/h, for seeds from 0.47 kg/h to 0.33 kg/h. fluff, and the output of lint seeds from the working chamber is accelerated, there is an effective implementation of the linting process.